REDUCTION OF ENERGY CONSUMPTION OF FRICTION ASSEMBLY OF STRIP-PAD BRAKES OF DRILLING WINCHES - Kindrachuk, Myroslav; Skrypnyk, Vasyl; Vasylyshyn, Yaroslav; Voznyi, Andrii; Vasilyshyn, Vitaliy; Kharchenko, Volodymyr (Problems of Friction and Wear, 2025)
The materials of the article consider the issue of forced air-liquid cooling of the composite pulley of the belt-pad brake of a drilling winch. The brake pulley consisted of two parts, between which there is a gap and they are connected by metal thermal bridges with offset holes. The lower part of the pulley rim has a polished surface that interacts with the heat carrier located in the pulley rim chamber. Air and liquid forced cooling of the working surface of the belt-pad brake pulley rim is described separately. An assessment of the efficiency of forced cooling of the brake friction pairs is given. The heat transfer coefficient from both metallic and non-metallic friction elements of band-pad brakes can be increased by creating a developed heat exchange surface (using fins or pulley deflectors, making air intakes in the form of ribs, etc.), as well as by placing turbulators in the brake parts, which can be made in the form of a hole in the flange or a system of holes and channels in the pulley. The location of bellows above the brake band, interacting with the pulley flange and connected to the holes in the brake band and in the friction lining, or confusers, diffusers, vortex tubes in pairs "pulley - lining" or "lining - band section" also intensifies the cooling of the friction unit. The listed design solutions are aimed at changing the thermodynamic parameters of the air circulating between the working parts of the brake and, as a result, increasing the efficiency of natural-forced cooling. In a self-ventilated brake disc, half-discs are connected by cylindrical studs. All elements of the self-ventilated disc are hollow and filled with 2/3 of their volume with liquid. In this way, indirect cooling of the friction belts of the disc-pad brake of the vehicle is carried out.